Reduced Plasma Eicosapentaenoic Acid–Arachidonic Acid Ratio in Peripheral Artery Disease. (February 2013) - Fujihara, Masahiko; Fukata, Mitsuhiro; Odashiro, Keita; Maruyama, Toru; Akashi, Koichi; Yokoi, Yoshiaki
A reduced ratio of plasma eicosapentaenoic acid–arachidonic acid (EPA-AA) is a newly recognized atherosclerotic risk factor. This ratio has not been fully investigated in peripheral artery disease (PAD). Seventy Japanese patients with atherosclerotic risk factors were enrolled and divided into 2 groups, those with PAD (group A: n = 38) and those without PAD (group B: n = 32). The EPA-AA ratio ( P = .001) and ankle–brachial index (ABI: P < .001) in group A were significantly lower than those in group B. Univariate and multivariate analyses demonstrated that EPA-AA, ABI, and prescription of clopidogrel had significant correlation with PAD. Given the appropriate cutoff values, EPA-AA (odds ratio [OR] = 11.7, 95% confidence interval [CI] = 3.0-45.8; P < .001) and ABI (OR = 44.0, 95% CI = 5.4-358.5; P < .001) are factors independently associated with PAD. In conclusion, this study demonstrated that reduced plasma EPA/AA may underlie PAD at least in Japanese.